Selling culture: HOW ENGLISH AND UZBEK PROMOTIONAL TEXTS FRAME UZBEKISTAN FOR DOMESTIC VS. FOREIGN AUDIENCES - Abdisoatova Dilnoza; Elmuradova Gulrux Karimaliyevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Tourism promotional texts rely heavily on metaphor to transform destinations into objects of desire. This article compares the metaphorical framing of Samarkand in one English-language text (Embassy of Uzbekistan) and one Uzbek-language text (Afisha.uz). Drawing upon cognitive metaphor theory, the analysis reveals systematic differences: the English text deploys metaphors of spectacle, timelessness, and fairy-tale orientalism, framing Samarkand as an exotic treasure for foreign discovery. The Uzbek text employs metaphors of vitality, organic wholeness, and sensory immersion, framing Samarkand as a living heritage for domestic reconnection. These contrasting metaphorical repertoires demonstrate how the same destination is linguistically constructed for different audiences, serving both promotional and nation-affirming functions.